2022
DOI: 10.3390/ijms23031450
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Pheochromocytomas and Paragangliomas Determine the Therapeutical Approach

Abstract: Pheochromocytomas and paragangliomas are the most heritable endocrine tumors. In addition to the inherited mutation other driver mutations have also been identified in tumor tissues. All these genetic alterations are clustered in distinct groups which determine the pathomechanisms. Most of these tumors are benign and their surgical removal will resolve patient management. However, 5–15% of them are malignant and therapeutical possibilities for them are limited. This review provides a brief insight about the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 136 publications
0
34
0
1
Order By: Relevance
“…To address this problem, two key features associated with the tumor immunotherapy need to be elucidated—tumor heterogeneity and the tumor microenvironment (Hegde & Chen, 2020; Li et al , 2018; Liu et al ., 2023; Liu et al ., 2022; Zhang & Zhang, 2020). Regarding PCC heterogeneity, genomic studies have confirmed the inter-individual heterogeneity based on driver mutations (Dahia, 2014; Jhawar et al , 2022; Sarkadi et al , 2022; Toledo et al ., 2017). However, there is lack of relevant research on intra-tumoral heterogeneity, which has an impact on disease progression and sensitivity to immunotherapy (Vitale et al , 2021).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To address this problem, two key features associated with the tumor immunotherapy need to be elucidated—tumor heterogeneity and the tumor microenvironment (Hegde & Chen, 2020; Li et al , 2018; Liu et al ., 2023; Liu et al ., 2022; Zhang & Zhang, 2020). Regarding PCC heterogeneity, genomic studies have confirmed the inter-individual heterogeneity based on driver mutations (Dahia, 2014; Jhawar et al , 2022; Sarkadi et al , 2022; Toledo et al ., 2017). However, there is lack of relevant research on intra-tumoral heterogeneity, which has an impact on disease progression and sensitivity to immunotherapy (Vitale et al , 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Regarding PCC heterogeneity, genomic studies have confirmed the inter-individual heterogeneity based on driver mutations (Dahia, 2014;Jhawar et al, 2022;Sarkadi et al, 2022;Toledo et al, 2017). However, there is lack of relevant research on intra-tumoral heterogeneity, which has an impact on disease progression and sensitivity to immunotherapy (Vitale et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine chromaffin tissue tumors that may produce catecholamines (5). About 80-85% of PPGLs come from the adrenal medulla, which is called pheochromocytoma, whereas about 15-20% of PPGLs come from the sympathetic or parasympathetic paravertebral ganglia, which is called paragangliomas (6).…”
Section: Discussionmentioning
confidence: 99%
“…La deleción del gen TMEM127 descrita produce una proteína truncada o ausente asociada exclusivamente al desarrollo de feocromocitoma, aunque existen reportes de otras neoplasias malignas asociadas como cáncer de células renales, cáncer de colon, leucemia mieloide aguda, ade-nocarcinoma pancreático, melanoma maligno y adenoma de paratiroides 5,11 . Mutaciones de este gen fueron descritas inicialmente el 2010, con una edad de diagnostico 40-50 años y el patrón de herencia es autosómico dominante 6 .…”
Section: Conclusiónunclassified